CHILDHOOD TRAUMA IN PARAMORE’S SONG THE ONLY EXCEPTION - Astika R. Pratiwi; Rizal Rafiuddin; Firdausy Alya Hasana; Lisma Ayu Arditha; Rommel Utungga Pasopati; Ni Nyoman Sarmi; Dimas Eko Saputro (Seminar Nasional Hasil Riset dan Pengabdian, 2025)
>This study investigates the representation of childhood trauma in Paramore’s song The Only Exception by analyzing its figurative language through the lens of trauma theory. Using a qualitative descriptive approach, the research explores how the lyrics articulate the long-term psychological effects of witnessing parental conflict and how figurative devices, such as metaphor, personification, hyperbole, paradox, and repetition, convey the narrator’s emotional struggles. Drawing on Herman’s (1992) and Perry’s (2001) theories of trauma alongside contemporary scholarship on childhood adversity, this study demonstrates that the song reflects trauma not only as an individual experience but also as a cultural narrative. The results highlight how trauma manifests in avoidance strategies, mistrust of love, and fear of intimacy, yet also reveal the possibility of resilience and gradual healing. By positioning popular music as literature, the research underscores how songs can serve as testimonies of private pain that become accessible to a wider audience, turning trauma into a shared cultural text. In conclusion, this study contributes to the fields of literature, cultural studies, and psychology by showing how music operates as both artistic expression and psychological discourse.